Energy Efficiency Consumption of Building Planning Based on Indonesia Green Building Rules: A Case Study - Salsabila Ramadhanti; Yatnanta Padma Devia; Alwafi Pujiraharjo (Engineering Science Letter, 2025)
This study evaluates the energy performance of the Tower B building in Riau Province, Indonesia, based on green building assessment criteria, with a focus on energy use efficiency. The initial design showed a total energy consumption of 2,255,923 kWh/year, corresponding to an Energy Use Intensity (EUI) of 95.46 kWh/m²/year, and earned a moderate energy score of 30 out of 46. Two operational strategies were proposed to address inefficiencies: (1) reducing the number of elevator units from six to four, and (2) implementing separate grouping of luminaires based on daylight exposure. Simulation results indicated that these strategies could reduce energy consumption in the elevator system by 33% and in the lighting system by 13%, without compromising user service standards. The combined application of both measures reduced total building energy use to 1,949,861 kWh/year (EUI 82.51 kWh/m²/year), yielding a 29% overall reduction and increasing the energy efficiency score to 38. While the results are promising, further research is needed to validate implementation through sensitivity analysis, behavioral modeling, and integration into regulatory frameworks. This study highlights the potential of adaptive operational strategies in optimizing building energy performance in tropical urban contexts.